Short film workshop and people with mental illness: art therapy technique and resource - Caravaca-Llamas, Carmen; Sáez Olmos, José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This experience describes the conclusions drawn from a short film workshop as a therapeutic method to work on empowerment and emotional expression skills with a group of people with mental illness, users of a day center. The end of the workshop culminates with a video forum and the recording of a video for an annual short film contest on mental health. For the evaluation of the workshop, a qualitative methodological process based on the discussion group was used. Most highlighted the positive experiences resulting from the program and the positive effects, especially on a creative and emotional level.